2003
DOI: 10.1177/008124630303300202
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Caring for Patients with Alzheimer's Disease: Their Strengths and Risk of Burnout

Abstract: This study focused on the relationship between psychofortigenic factors and psychological burnout among nursing staff at institutions where patients with Alzheimer's disease, as well as other conditions, are hospitalized. Psychofortigenesis relates to the term ‘salutogenesis’ and refers to the origin of psychological strengths. It can thus be regarded as the opposite of psychopathogenesis. There is evidence of high levels of burnout among nursing staff in South Africa and thus the question arises as to which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Given that numerous researchers demonstrated that life satisfaction was related to aging (e.g., Tucker et al 2006) and work stress (e.g., Heyns et al 2003), the selection of university students, elderly adults and correctional officers as the samples of the present study was reasonable. Gathering data from different samples is necessary in order to improve the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that numerous researchers demonstrated that life satisfaction was related to aging (e.g., Tucker et al 2006) and work stress (e.g., Heyns et al 2003), the selection of university students, elderly adults and correctional officers as the samples of the present study was reasonable. Gathering data from different samples is necessary in order to improve the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have utilized the SWLS with undergraduate students (Gouveia et al 2009), adults (Tucker et al 2006), and elderly individuals (e.g., Elavsky et al 2005;Minardi and Blanchard 2003). Furthermore, researchers have studied the influence of subjective well-being (as measured by SWLS) on individuals experiencing stressful life events, such as mothers of school-aged children with cerebral palsy (Skok et al 2006), caregivers of individuals with dementia (McConaghy and Caltabiano 2005), physicians, teachers (Gouveia et al 2009), and nurses (Heyns et al 2003).…”
mentioning
confidence: 99%
“…Workload was a significant predictor of emotional exhaustion (β = 0.547, p = < 0.001) and work/family interface as a source of stress was a significant predictor of depersonalization (β = 0.296, p = 0.004). Emotional intelligence was a moderator of the relationship between stress and burnout, explaining 59.5% of the variance in the emotional exhaustion and 23.9% of the variance in the depersonalization subscale of burnout.Heyns, 2003 [77]South AfricaNurses caring for patients with Alzheimer’s disease ( N = 226)MBIEmotional exhaustion (mean ± SD): 14.3 ± 10.3Depersonalization: 4.5 ± 5.6Personal accomplishment: 36.3 ± 8.226% reported high emotional exhaustion, 21% high depersonalization, and 66% low personal accomplishment.Sense of Coherence Scale, Fortitude Questionnaire scores, age, years of experience, hours of work, hours of direct attention to patients, qualifications and institution predicted scores on the burnout subscales ( p < 0.01).Ifeagwazi, 2005 [78]NigeriaNurses from a teaching hospital ( N = 91)MBITotal burnout (mean ± SD):widowed nurses: 3.1 ± 0.3 married nurses: 2.6 ± 0.5Widowed nurses reported significantly higher burnout than married nurses ( p < 0.001). There were significant differences between hospital units on mean burnout symptoms reported ( p < 0.01), with nurses on the operating theater unit having higher mean burnout scores than nurses on the postnatal, casualty, labor, surgical and out-patient units.…”
Section: Methodsmentioning
confidence: 99%
“…The FORQ also correlated with measures of psychological distress as well as with measures of selfappraisal (i.e., self-esteem), social support and family environment. Additional support for the reliability and validity of the FORQ has come from several South African studies that have reported reliability coefficients between 0.77 and 0.88 (Heyns et al, 2003;Wissing, Wissing, du Toit, & Temane, 2006;Wissing & Temane, 2013). These authors also used structural equation modelling to confirm the factor structure of the FORQ.…”
Section: Instrumentsmentioning
confidence: 96%